Experimental Cholera in Germfree Suckling Mice - Shimamura, Tadakatsu (1981)
Vibrio cholerae V86 El Tor Inaba caused experimental cholera in germfree ICR suckling mice. Sucklings born of gnotobiotic mothers monoassociated with the same strain were completely protected against live oral homologous challenge.